Grass blade-like microparticle MnPO4·H2O prepared by a simple precipitation at room temperature - Boonchom, Banjong; Baitahe, Rattanai; Joungmunkong, Zongporn; Vittayakorn, Naratip (My University, 2010)
Grass blade-like microparticle MnPO4·H2O was synthesized by a simple precipitation at room temperature using a mixture of manganese sulphate monohydrate, phosphoric acid and water at pH=7. The thermogravimetric study indicates that the synthesized compound is stable below 500°C and its final decomposed product is Mn2P2O7. The pure monoclinic phases of the synthesized MnPO4·H2O and its final decomposed product Mn2P2O7 are verified by XRD data. FTIR spectra indicate the presences of the PO43- ion and water molecules in the MnPO4·H2O structure and the P2O74- ion in the Mn2P2O7 structure. The thermal stability, crystallite size, and grass blade-like microparticle of MnPO4·H2O in this work are different from previous reports, which may be caused by the starting reagents and reaction condition for the precipitation. © 2010 Elsevier B.V.
Keywords: FTIR; Grass blade-like particle MnPO4·H2O; Powder synthesis; Thermogravimetric analysis